A study on the overall variance and void architecture on MEX-PLA tensile properties through printing parameter optimisation - Mirza Faizaan; Satish Shenoy Baloor; Srinivas Nunna; Ravindra Mallya; Sathish Rao Udupi; Chandrakant Ramanath Kini; Sitarama Raju Kada; Claudia Creighton (Scientific Reports)
Abstract This study investigates the influence of printing parameters on the tensile properties and void architecture of poly(lactic) acid (PLA) parts fabricated using the fused filament fabrication (FFF) technique. Two Taguchi optimisation methods were employed to identify the optimal parameter combinations for maximising tensile performance. The results revealed a positive correlation between tensile performance and nozzle diameter (ND). Notably, the analysis of the coefficient of variance (COV) studies revealed that both tensile strength and modulus exhibited minimal variation within a tight range of 5.5%, suggesting a high degree of process consistency in achieving desired mechanical properties regardless of the chosen parameters within the investigated range. Micro-computed tomography (micro-CT) analysis was used to quantify void characteristics within the as-printed samples. Micro-CT analysis confirmed the influence of ND and layer thickness (LT) on void architecture. By establishing structure–property relationships, the study revealed that larger NDs paired with finer LTs yielded superior tensile properties due to reduced void content. This work highlights the interplay between printing parameters, void architecture, and the resulting mechanical behaviour of MEX-based PLA parts.